2012
DOI: 10.1038/nature10832
|View full text |Cite
|
Sign up to set email alerts
|

Stability criteria for complex ecosystems

Abstract: Forty years ago, May proved that sufficiently large or complex ecological networks have a probability of persisting that is close to zero, contrary to previous expectations. May analysed large networks in which species interact at random. However, in natural systems pairs of species have well-defined interactions (for example predator-prey, mutualistic or competitive). Here we extend May's results to these relationships and find remarkable differences between predator-prey interactions, which are stabilizing, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

78
1,473
13
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,076 publications
(1,574 citation statements)
references
References 31 publications
78
1,473
13
10
Order By: Relevance
“…The lack of nestedness in the dominant quantitative structure of empirical networks is consistent with our mathematical treatment of the local stability of nested structures. Although local stability analysis captures only one aspect of ecological system dynamics, its mathematical tractability provides a good starting point for assessing the dynamical consequences of network structure 25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of nestedness in the dominant quantitative structure of empirical networks is consistent with our mathematical treatment of the local stability of nested structures. Although local stability analysis captures only one aspect of ecological system dynamics, its mathematical tractability provides a good starting point for assessing the dynamical consequences of network structure 25 .…”
Section: Resultsmentioning
confidence: 99%
“…If all of the signs are negative then the equilibrium point is stable. Contemporary work has shown that nested mutualistic networks are less likely to be stable than their random counterparts 25 . We now demonstrate that a nested structure within M minimizes local stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the degree of nestedness varies among networks. Recently 5,10 , it has been argued that nestedness increases biodiversity and begets stability, but these results are in conflict with robust theoretical evidences showing that ecological communities with nested interactions are inherently less stable than unstructured ones 12,14,15 and that mutualism could be detrimental to persistence 11,15 . We aim to elucidate general optimization mechanisms underlying network structure and its influence on community dynamics and stability.…”
mentioning
confidence: 99%
“…The relatively low abundances of the specialist species make them more vulnerable to extinction and results in correspondingly lower community resilience, as measured by the maximum real part of the eigenvalues of the community matrix community ( Figure 4B). The advantage of having a high total population leading to increased robustness against extinction due to demographic fluctuations, carries with it the cost associated with a lower resilience -the optimized network recovers from perturbations on a longer timescale than its random counterpart 12,14,27 (Figure 4C). …”
mentioning
confidence: 99%